Study of prestrain influence for the prediction of the necking occurrence - Thang, Nguyen Nhat (Vietnam Journal of Mechanics, 1999)
This paper contains experimental results for mechanical characteristics of a mild steel sheet. The determination of the forming limit stress curve for solicitation along two direction is drawn. Study of pestraint influence from the limit stress diagram is presented.